Consensus Guidelines of Russian Society of Radiology (RSR) and Russian Association of Specialists in Ultrasound Diagnostics in Medicine (RASUDM) «Role of Imaging (X-ray, CT and US) in Diagnosis of COVID-19 Pneumonia» (version 2) - V. E. Sinitsyn; I. E. Tyurin; V. V. Mitkov (Вестник рентгенологии и радиологии)
The paper presents Consensus Guidelines of Russian Society of Radiology (RSR) and Russian Association of Specialists in Ultrasound Diagnostics in Medicine (RASUDM) «Role of imaging (X-ray, CT and US) in diagnosis of COVID-19 pneumonia» (version 2) of the Russian Society of Radiology and the Russian Association of Specialists in Ultrasound Diagnostics in Medicine.The guidelines list radiological techniques for lung diseases, which are used in coronavirus COVID-19 infection (chest X-ray, lung computed tomography (CT), and lung ultrasound (US), diagnostic algorithm, and follow-up study. The guidelines propose the models of the work of radiological rooms/departments of a healthcare facility, the procedure for conducting an examination, and recommendations for providing a description and assessing changes in the lung and chest in existing/suspected COVID-19-related pneumonia and present the schemes of X-ray and CT protocols at the initial examination and assessment of the changes.Chest X-ray has a low sensitivity for detecting initial changes in the first days of the disease and is not recommended for early diagnosis. Mobile radiography is an important tool for diagnosis of lung pathology in the intensive care units.CT is the most sensitive technique in detecting lung changes characteristic of COVID-19-related pneumonia. It is advisable to use CT for the initial evaluation of thoracic organs in patients with severe and progressive forms of the disease, as well as for the differential diagnosis and follow up.Lung US in patients with suspected/known COVID-19-related pneumonia is an additional imaging method that does not replace or exclude X-ray and CT. If the correct procedure is followed, correct indications are selected, and trained medical personnel is available, this study is highly sensitive in detecting interstitial changes and consolidations in lung tissue, but only in their subpleural location. The US data do not always allow definite determination of the reasons for the occurrence and/or actual extent of lung tissue changes.Standard reporting guidelines (CT, X-ray) about the possibility of COVID-19 pneumonia and its severity should be used.The follow up using CT, X-ray, or US depends on the clinical indications that necessitate dynamic assessment. The recommended frequency of repeat CT and X-ray in patients having no substantial changes in their clinical condition outside the intensive care units is not more than once every 5-7 days. An objective assessment of the time course of changes is possible only when comparing the data of the same type of study.